1996
DOI: 10.1111/j.1151-2916.1996.tb08574.x
|View full text |Cite
|
Sign up to set email alerts
|

Auger Electron Spectroscopy of Aluminum Nitride Powder Surfaces

Abstract: The chemical states of powder surfaces depend on the manufacturing processes of the powders. The surface chemistry of three different commercial AIN powders, which are processed by carbothermal nitridation of Al2O3, chemical vapor deposition (CVD), and direct nitridation of aluminum, were evaluated by using Auger electron spectroscopy (AES). In order to obtain reference AES spectra of aluminum compounds, α‐, γ‐, θ‐Al2O3, γ‐AIOOH, γ‐AION, and sintered AIN were also examined. Line shapes of aluminum LVV; Al(LVV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Our present DRIFT analysis has revealed that the surface oxide of powders A and C possesses a boehmite‐like structure, and that of powder B is θ‐Al 2 O 3 like. This analysis has further confirmed and completed the previous TPD 20 and AES 21 studies, and is in agreement with the hydrolytic degradation–resistance properties observed recently 6,7 . In addition, the bands at 2245 and 2120 cm −1 observed above 200°C, which were not identified previously, might be assigned to OCN and CN groups, respectively, according to our analysis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our present DRIFT analysis has revealed that the surface oxide of powders A and C possesses a boehmite‐like structure, and that of powder B is θ‐Al 2 O 3 like. This analysis has further confirmed and completed the previous TPD 20 and AES 21 studies, and is in agreement with the hydrolytic degradation–resistance properties observed recently 6,7 . In addition, the bands at 2245 and 2120 cm −1 observed above 200°C, which were not identified previously, might be assigned to OCN and CN groups, respectively, according to our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…showed a much stronger one. A shoulder at 3765 cm −1 of the 3730 cm −1 band of powder B, although weak and with its intensity comparable with the noisy bands, could be due to the existence of Al IV –OH if the previous TPD 20 and AES 21 results are considered. In addition, in the carbothermal reduction and nitridation process, a postburning treatment at a moderate temperature (normally <1000°C) is usually necessary to remove residual carbon, and this could be the reason for the presence of θ‐Al 2 O 3 ‐like surface.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The higher the content of oxygen, the higher was the length of the initial stage. According to an auger electron spectroscopy (AES) study of AlN powder surfaces, the chemical states of the powder surfaces depend on the manufacturing processes for the preparation of the powders . The AES analysis indicated the presence of an oxide‐like‐Al 2 O 3 containing an AlON phase on the surface of AlN powder prepared by the carbothermal‐nitridation process, while those prepared by CVD and the direct‐nitridation method are covered by an oxide‐like‐Al 2 O 3 with an oxygen diffusion layer and do not contain the AlON phase.…”
Section: Introductionmentioning
confidence: 99%